Comparison of the prevalence and trends of Hepatitis B among blood donors in Tripoli, Misurata and Zleetin cities: Two years before and after Libyan incidences (Journal of Academic Research, 2018)
Hepatitis B virus is considered as a serious public health problem. Infection of this virus might lead to more serious clinical consequences. This study was conducted to estimate and compare the prevalence and trend of HBV infection among blood donors of three cities in Libya, Tripoli, Misurata and Zleetin and to explore the effect of Libyan incidences on the trend of the infection. A retrospective study was carried out on 72146 nationwide voluntary blood donors in four blood banks, covering the three cities over a period of four years (2009-2013), where serologic screening assay for HBsAg was performed. Findings showed statistically significant differences (P0.05) after Libyan incidences with no statistically significant difference. Sensitive tests such as nucleic acid amplification are recommended for more accurate results